Extended BGK Boltzmann for Dense Gases (Communications in Computational Physics, 2020)
An alternate BGK type formulation of the Enskog equation has been recentlyproposed [1]. It was shown that the new model has a valid H-theorem and correct thermal conductivity. We propose Lattice Boltzmann (LB) formulation of this new Enskog-BGK model. The molecular nature of the model is verified in case of shear flow bycomparing the predicted normal stress behavior by the current model with the prediction of molecular dynamics simulations. We extend the model for multiphase flow byincorporating attractive part as Vlasov type force. To validate multiphase formulation,the results of 3D simulations of a condensing bubble in a periodic box are presented.